x(x +1)(x+2)(x+3)=24
indicatie:x^2 + 3x=t
Răspunsuri la întrebare
Răspuns de
1
Răspuns:
Explicație pas cu pas:
x(x+1)(x+2)(x+3) = 24
⇔ x(x+3)(x+1)(x+2) = 24
⇔ (x²+3x)(x²+2x+x+2) = 24
⇔ (x²+3x)(x²+3x+2) = 24
Notez x²+3x = t:
⇔ t(t+2) = 24
⇔ t²+2t-24 = 0
- Δ = 2² - 4·1·24 = 100 = 10²
- t₁,₂ = (-2 ± 10)/2
① t = (-2 - 10)/2 ⇒ t = -6 ⇒ x²+3x = -6
⇒ x²+3x+6 = 0
- Δ = 3² - 4·1·6 = 9-24 = -15 < 0
⇒ x ∈ Ф
② t = (-2 + 10)/2 ⇒ t = 4 ⇒ x²+3x = 4
⇒ x²+3x-4 = 0 ⇒ x²-x+4x-4 = 0
⇒ x(x-1)+4(x-1) = 0 ⇒ (x-1)(x+4) = 0
⇒ x ∈ {-4; 1}
Din ① ∨ ② ⇒ S = {-4; 1}
Alte întrebări interesante
Ed. tehnologică,
8 ani în urmă
Limba română,
8 ani în urmă
Ed. tehnologică,
8 ani în urmă
Matematică,
8 ani în urmă
Istorie,
9 ani în urmă
Limba română,
9 ani în urmă